Viewpoint and the fabric of meaning form and use of viewpoint tools across languages and modalities - Dancygier, Barbara 1952-; Lu, Wei-lun; Verhagen, Arie 1951- (De Gruyter Mouton, 2016)
This volume explores the cross-linguistic diversity, and possibly inconsistency, of the span of linguistic means that signal reported speech and thought. The integration of broad linguistic (viewpoint in conversation and narrative) and cognitive (theory of mind and understanding the inner life and thought of others) strategies for handling mixed points of view will be considered
Keywords: Kognitive Linguistik; Diskursanalyse; Perspektive; Indirekte Rede; Aufsatzsammlung